Evaluation of gingival crevicular fluid and serum tartrate-resistant acid phosphatase levels in subjects with clinically healthy periodontium and chronic periodontitis - A clinico-biochemical study - Harshitha Baddam; Gopinath Vivekanandan; Kameswari Kondreddy; Swapna Peddi; Pranjal Praveen Chitnis; Yash Pal Singh; Rahul V C Tiwar (Wolters Kluwer Medknow Publications, 2021)
Background: Periodontitis is a chronic inflammatory disease with conglomerate etiology making it difficult to diagnose at the early stages. Potential biomarkers in gingival crevicular fluid (GCF) would determine the presence of the current disease activity, predict sites vulnerable for future breakdown, and assess the response to periodontal interventions. Merely elevated levels of inflammatory soft-tissue markers do not indicate bone destruction. Since there is no single ideal biomarker established, bone-related biomarkers such as telopeptide of type I collagen, osteocalcin, calprotectin, osteopontin, and tartrate-resistant acid phosphatase (TRAP) seem to hold great promise as predictive markers to determine bone destruction and active phases in the disease progression. The present study is intended to explore the biologic plausibility of the levels of TRAP in health and chronic periodontitis. Materials and Methods: The present cross-sectional clinico-biochemical study comprised 30 systemically healthy subjects with 15 periodontally healthy and 15 chronic periodontitis subjects who were age and gender matched. GCF and blood samples were collected from all the patients. TRAP estimation was done in both the samples using an enzyme-linked immunosorbent assay kit. The data were analyzed using independent t-test and Pearson correlation test. Results: Serum and GCF TRAP levels in chronic periodontitis subjects were significantly higher when compared to the periodontally healthy group. There were no significant correlations found among serum and GCF TRAP levels with increasing age and gender in both the groups. An increase in disease severity, i.e., increase in probing pocket depth and clinical attachment level, did not show correlation with the GCF and serum TRAP levels in the chronic periodontitis group. Conclusion: Based on the findings of the present study, increased GCF TRAP levels in chronic periodontitis seem to be a potential marker for identifying ongoing periodontal destruction.